Exploring the Size‐Dependent Hydrogen Storage Property on Ti‐Doped Bn Clusters by Diatomic Deposition: Temperature Controlled H2 Release. Issue 7 (19th May 2021) - Rodríguez‐Kessler, Peter L.; Rodríguez‐Domínguez, Adán R.; MacLeod‐Carey, Desmond; Muñoz‐Castro, Alvaro
Abstract: The hydrogen storage properties of Ti‐doped B n ( n = 3 − 12 ) clusters are investigated by using the "diatomic deposition method" with further evaluation by density functional theory computations. The results show that TiB n ( n = 7 − 9 ) clusters possess the ability to storage up to four H2 molecules, reaching a mass fraction of 6.12%. Further, the hydrogen release temperature is analyzed by molecular dynamics simulations with a variable temperature. It turns out that the TiB7 and TiB9 clusters release the H2 molecules at T ≲ 700 K, while TiB8 requires higher temperature due to stronger interactions with the H2 molecules, confirmed by the electronic density of states. The size‐dependent properties and odd–even nuclearity on the clusters can be useful for applications with controlled temperature. These results serve for further design of novel materials with reversible and controlled hydrogen storage properties based on TiB7 /TiB9 motifs. Additionally, new lower‐energy isomers for TiB4 and TiB9 clusters were found within the accuracy of the all‐electron triple‐ζ Slater [slater type orbital (STO)‐Triple‐zeta basis set(TZP)] basis set. Abstract : The diatomic deposition method is applied for investigating the hydrogen storage properties of Ti‐doped B n ( n = 3–10) clusters. The hydrogen release temperature is analyzed by molecular dynamics simulation. Depending on the number of boron atoms, the release temperature occurs around T = 700 K for TiB7 and TiB9, while TiB8 requires higher temperature due to stronger interactions with the H2 molecules.